Uma introdução a relatividade especial utilizando materiais multimídias - Nasser, Bruno Birolli (2010)
This paper presents the development of a course on the subject of special relativity to high school, and the results obtained with its application in the classroom. As background material for this course was prepared a supporting text for the student, as well as a manual to support the teacher. With the help of the software PowerPoint and Isadora were produced, too, multimedia materials, such as animations and interactive simulations in order to make easier the process of meaningful learning of concepts and phenomena of the theory of special relativity.